2015
DOI: 10.1155/2015/608435
|View full text |Cite
|
Sign up to set email alerts
|

Modern Evaluation of Liquisolid Systems with Varying Amounts of Liquid Phase Prepared Using Two Different Methods

Abstract: Liquisolid systems are an innovative dosage form used for enhancing dissolution rate and improving in vivo bioavailability of poorly soluble drugs. These formulations require specific evaluation methods for their quality assurance (e.g., evaluation of angle of slide, contact angle, or water absorption ratio). The presented study is focused on the preparation, modern in vitro testing, and evaluation of differences of liquisolid systems containing varying amounts of a drug in liquid state (polyethylene glycol 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…26 . These results confirmed conclusions of the previous study 22 , where was observed that preparation of liquisolid systems by spraying in the fluid bed equipment led to more uniform tablets in comparison to the simple blending method.…”
Section: Drug Contentsupporting
confidence: 92%
See 4 more Smart Citations
“…26 . These results confirmed conclusions of the previous study 22 , where was observed that preparation of liquisolid systems by spraying in the fluid bed equipment led to more uniform tablets in comparison to the simple blending method.…”
Section: Drug Contentsupporting
confidence: 92%
“…However, liquisolid system with acceptable flowing and compressible properties can be prepared only if a maximum liquid load of the carrier material is not exceeded 30 . Therefore, according to the previous study 22 , value of liquid load factor (L f ) (the weight ratio between the drug in liquid state and the carrier material) was established to 0.6 and excipient ratio (R) (the weight ratio between the carrier and the coating material) to 50 in all formulations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations